2019
DOI: 10.3390/separations6010003
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Uptake in Tumor Cells: Quantification and Size Distribution by sp-ICPMS

Abstract: Gold nanoparticles (AuNPs) are increasingly studied for cancer treatment purposes, as they can potentially improve both control and efficiency of the treatment. Intensive research is conducted in vitro on rodent and human cell lines to objectify the gain of combining AuNPs with cancer treatment and to understand their mechanisms of action. However, using nanoparticles in such studies requires thorough knowledge of their cellular uptake. In this study, we optimized single particle ICPMS (sp-ICPMS) analysis to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…The relatively short incubation time was particularly helpful to counter potential delays in beam delivery, which are inherent to experiments at accelerator facilities. Previous studies showed that AuNP update and cytotoxicity are cell type dependent, with a preferential uptake by cancer cells in comparison to normal cells ( 62 65 ). This brings us to one of the main limitations of the current proof of principle study, since only one non-cancerous cell type was used for this evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively short incubation time was particularly helpful to counter potential delays in beam delivery, which are inherent to experiments at accelerator facilities. Previous studies showed that AuNP update and cytotoxicity are cell type dependent, with a preferential uptake by cancer cells in comparison to normal cells ( 62 65 ). This brings us to one of the main limitations of the current proof of principle study, since only one non-cancerous cell type was used for this evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Upon completion of all three digestion phases (oral, gastric and intestinal), the total Ag content in both of the IVD AgNPs suspensions and the AgNO 3 solution was similar to that of the corresponding pristine suspensions and solution, except for the highest concentration of both AgNPs, with the total Ag content being $10% and $40% lower for (LA) and (Cit) AgNPs, respectively. The reduction in total Ag content of samples taken from the highest concentrations could be due to a lower (analytical) recovery due to adsorption of AgNPs to the digestion matrix and tubing, and/or to the short centrifugation step applied to the AgNPs samples after digestion to spin down large protein precipitates before ICP-MS measurement (Versantvoort et al 2005) to which the AgNPs could potentially adsorbed (Noireaux et al 2019). This centrifugation set is required to avoid the presence of large proteins that destabilize the plasma of the ICP-MS (Noireaux et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in total Ag content of samples taken from the highest concentrations could be due to a lower (analytical) recovery due to adsorption of AgNPs to the digestion matrix and tubing, and/or to the short centrifugation step applied to the AgNPs samples after digestion to spin down large protein precipitates before ICP-MS measurement (Versantvoort et al 2005) to which the AgNPs could potentially adsorbed (Noireaux et al 2019). This centrifugation set is required to avoid the presence of large proteins that destabilize the plasma of the ICP-MS (Noireaux et al 2019). On the other hand, a significant reduction in the mass-and number-based AgNPs content was observed for both AgNPs upon completion of all digestion phases, demonstrating that the in vitro digestion could induce dissolution, aggregation, or protein binding of the AgNPs (B€ ohmert et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…After euthanasia, each tumor was resected, weighed, and immediately digested through a dissolution in acid for ICP–MS analyses [ 29 , 30 ]. Specifically, the tumor was dissolved in 10 mL of a 3:1 ( υ / υ ) solution of HNO 3 (68%) and H 2 O 2 (50%) and allowed to dissolve overnight.…”
Section: Methodsmentioning
confidence: 99%